Improving WTO Transparency: India's Shadow Farm Support Notifications - Gopinath, Munisamy (2009)
Munisamy Gopinath, Professor, Dept of Agricultural & Resource Economics, Oregon State University 14th March-15th March 2008, International Food Policy Research Institute, Washington D.C.